Teach yourself visually HTML and CSS - Wooldridge, Mike (Teach yourself visually., 2008)
"Are you a visual learner? Do you prefer instructions that show you how to do something - and skip the long-winded explanations? If so, then this book is for you. Open it up and you'll find clear, step-by-step screen shots that show you how to tackle more than 175 tasks involving HTML and CSS. Each task-based spread covers a single technique, sure to help you get up and running with HTML and CSS in no time"--Resource description page